Ejecución presupuestaria de ingresos y gastos del Gobierno Autónomo Descentralizado Municipal del Cantón Baba en el período 2020 – 2021. - Crespo Villavicencio, Kerlly Rosalía (2022)
This Case Study called "Income and Expenditure budget of the Municipal Decentralized Autonomous Government of Baba Canton in the period 2020 - 2021", is carried out with the purpose of analyzing the economic execution in the institution to determine how it relates to compliance of the planned goals, revealing in turn how the administrative management is being carried out in relation to the sources of income and the fulfillment of obligations. This project is structured under the Financial, Tax and Social Commitment Management research subline, prior to obtaining the third-level degree in Accounting and Auditing. The method to be used is inductive-deductive and the type of research is based on a descriptive methodology based on the interview addressed to the director of the financial department of the Municipal GAD of Baba Canton as a qualitative element that allows realistic information to be collected. It is planned to take as a reference the State of Budget Execution of both years, where both the income and expenses of the institution are detailed, managing to carry out its review and comparison of the codified budget with the accrued budget, obtaining the execution carried out in the 2020 and in the same way determine what is raised in 2021. The budgets may present variations at the time of their execution, which may influence their fulfillment, for this reason it is of vital importance that the Municipal GAD of Baba be able to take advantage of the resources that allow satisfying the needs of citizens, and that through their good execution are reflected in public works promoting the development and progress of the Canton. Through the current case study, it is intended to demonstrate that it is essential to analyze the importance of budget items in order to have knowledge about how these have been manipulations and therefore also know the different changes they have presented.